The Impact of Savings on Credits: a Case Study of Atwima Kwanwoma Rural Bank (2000-2007) - Donkor, Jacob (2011)
A long essay Submitted to the Department of Accounting and Finance Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirements for the Degree of Master of Business Administration, 2008